Analysis of food sources and nutrient intakes of Filipino breastfeeding mothers in 2018 and 2019 Expanded National Nutrition Survey - Imelda Angeles Agdeppa; Eva A Goyena; Josie P Desnacido; Apple Joy D. Ducay (Indonesian Nutrition Association, 2022)
Objectives: This study evaluated the food and nutrient intake of Filipino breastfeeding mothers and identified the top food sources of nutrients in their diet. Methodology: This study utilized the pooled data of the Food and Nutrition Research Institute’s 2018-2019 Expanded National Nutrition Survey (ENNS), covering a total of 8,491 breastfeeding mothers from the 79 provinces and highly urbanized cities (HUCs) in the Philippines. The ENNS employed a two-stage sampling design to cover the study participants. Data on dietary intake was collected through a two-day non-consecutive 24-hour food. Generated data were analyzed using STATA version 15.0. A PC-Software for Intake Distribution Estimation (PC-SIDE) was used in the estimation of inadequate intakes.